Peran Lingkungan Sekolah dalam Menumbuhkan Kesadaran Berbahasa Jawa Krama pada Peserta Didik SD Negeri Sitanggal 02 - Turoh Mas'amah; Laelia Nurpratiwiningsih; Dedi Romli Triputra (EduInovasi: Journal of Basic Educational Studies, 2025)
Based on the example that Javanese Krama is a level of Javanese language that shows politeness and respect in communication, but currently its use is decreasing among the younger generation. The school environment has an important role in preserving and fostering awareness of the Javanese Krama language. This study aims to describe the role of the school environment in fostering awareness of the Javanese Krama language in students of Sitanggal 02 Elementary School and identify supporting and inhibiting factors. The results of the study show that Sitanggal 02 Elementary School implements a Javanese Krama language strengthening program through three main components, namely daily habituation programs, integration in learning, and special regional language programs. The implementation of the Javanese Krama language program in the school environment has succeeded in fostering a character of respecting elders, improving the ability to communicate with polite language, strengthening local cultural identity, and fostering a sense of pride in regional languages. Some of the obstacles faced include a less supportive home environment, the influence of social media, and limited learning resources, but the school overcomes this by involving the role of parents, holding routine habituation activities, and providing interesting learning media.